Regenerative medicine applications in organ transplantation - Orlando, Giuseppe 1970-. (Amsterdam Boston Elsevier/AP, 2014)
Regenerative Medicine Applications in Organ Transplantation illustrates exactly how these two fields are coming together and can benefit one another. It discusses technologies being developed, methods being implemented, and which of these are the most promising. The text encompasses tissue engineering, biomaterial sciences, stem cell biology, and developmental biology, all from a transplant perspective. Organ systems considered include liver, renal, intestinal, pancreatic, and more.
Principles of regenerative medicine and cell,tissue and organ bioengineering -- Kidney -- Liver -- Heart -- Small bowel -- Endocrine pancreas and islets of langerhans -- Lung -- Composite tissues allotranplantation -- Immunosuppression-free transplantation in the regenerative medicine era.
Includes bibliographical references and index.
Keywords: Regenerative medicine; Transplantation of organs, tissues, etc; Organ Transplantation; Regenerative Medicine -- methods; Electronic books